Potensi Dodecanoic Acid dari Limbah dan Sampah Organik Komposit Sebagai Formulasi Fungisida Alami Pertanian - Muh. Azhari; Sari Marlina; Achmad Imam Santoso (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The organic household waste generated by people in the course of meeting their daily needs has the potential to be processed into useful products that benefit the agricultural sector and the environment in general. Organic residues found in waste and organic refuse such as soy-based tofu production waste and household organic waste like vegetable scraps contain organic compounds such as dodecanoic acid, which acts as a fungicide. This study employs a descriptive research design with a mixed-methods approach, utilizing Gas Chromatography-Mass Spectrometry (GC-MS) to identify the organic compounds in the final product. Organic materials such as organic waste and refuse are combined into a composite. The process involves pre-treatment, saccharification, fermentation, and pyrolysis stages. The resulting products are hydrosol and gas. Dodecanoic acid, an organic compound, was obtained at a concentration of 7,54% within the hydrosol and gas products. The product can be applied by spraying it onto plants affected by fungal infections, thereby influencing plant health and productivity. The product can be applied by spraying it onto plants affected by fungal infections that impact plant health and productivity.